Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fvets.2022.911330
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With Zinc Proteinate Increases the Growth Performance by Reducing the Incidence of Diarrhea and Improving the Immune Function of Dairy Calves During the First Month of Life

Abstract: Two experiments were conducted to identify the optimal dose of zinc proteinate (ZP) in the diet for dairy calves and then to compare early supplementation with the ZP or zinc methionine (ZM) on the growth performance, incidence of diarrhea, antioxidant status, and immune function of dairy calves during their first month of life. In Experiment 1, forty newborn female Holstein dairy calves were randomly divided into four groups (n = 10): a control group (without ZP supplementation, ZP0) or groups that received Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…Zinc is an essential trace mineral for humans and animals with effective antidiarrheal and growth promotion activities ( 28 , 29 ). Lower doses of zinc, especially in organic forms, can reduce diarrhea and promote the growth of young animals ( 10 , 15 , 25 ). In agreement with these findings, the present study found that dietary supplementation with ZnP linearly increased total DMI, ADG, and feed efficiency, thus increasing the final BW of preweaned dairy calves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc is an essential trace mineral for humans and animals with effective antidiarrheal and growth promotion activities ( 28 , 29 ). Lower doses of zinc, especially in organic forms, can reduce diarrhea and promote the growth of young animals ( 10 , 15 , 25 ). In agreement with these findings, the present study found that dietary supplementation with ZnP linearly increased total DMI, ADG, and feed efficiency, thus increasing the final BW of preweaned dairy calves.…”
Section: Discussionmentioning
confidence: 99%
“…The calves were randomly allocated to 5 groups of 12 using a random number generator (Microsoft Corp., WA, n = 12 each): a negative control group without extra zinc supplementation (CON group); three groups supplemented with 261 (L-ZnP group), 523 (M-ZnP group), and 784 (H-ZnP group) mg/day ZnP, equivalent to 40, 80, and 120 mg/day zinc, respectively; and one group supplemented with 232 mg/d ZnO, equivalent to 180 mg/day zinc (ZnO group). These doses were based on previous studies ( 15 , 22 , 23 ). The ZnP ( Q f = 327) was donated by the Mineral Nutrition Research Division, Institute of Animal Science, Chinese Academy of Agricultural Sciences (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace minerals, including zinc (Zn), play essential roles in animal feed due to their physiological functions, impact on immune and reproductive systems, and overall animal performance [1 1 ]. Zn, in particular, is involved in crucial physiological processes such as cell division, proliferation, deoxyribonucleic acid (DNA) synthesis, gene expression, and enzyme cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc methionine (ZM), a chelate of inorganic zinc and methionine, is composed of zinc sulfate complexed with methionine in a 1:1:1 ratio of zinc, methionine, and the sulfate anion [8]. It has been demonstrated that early supplementation with ZM could reduce diarrhea incidence and promote the growth performance of dairy calves [9][10][11]. Furthermore, ZM also has beneficial effects on lipid metabolism and shows a high level of bioavailability [12,13].…”
Section: Introductionmentioning
confidence: 99%